Designing Foundations on Natural Soil for Specified (Uniform) Settlement: Merancang Pondasi di Atas Tanah Alami untuk Pemukiman Tertentu (Seragam) - Salomovich, Tulakov Elmurad; Shavkatovna, Mamatkulova Zebinisso (Universitas Muhammadiyah Sidoarjo, 2024)
This study addresses the critical issue of differential settlement and long-term fracture prevention in building foundations. Mistakes in designing strip and column foundations on natural soil often lead to cracks due to uneven settlements, as traditional methods prioritize matching foundation base pressure to soil bearing resistance, often neglecting settlement calculations. This research highlights the importance of incorporating settlement analysis into foundation design. A comparative review of existing methods and field data reveals significant disparities between standard design approaches and those considering settlement. Findings show that foundations designed with consistent settlement criteria exhibit better structural strength and reduced crack formation. The study underscores the need for a fundamental shift in foundation design procedures to include settlement analysis, ensuring the long-term durability and safety of buildings. Highlights: Traditional foundation design often neglects settlement calculations, leading to structural issues. Incorporating settlement analysis results in stronger, more durable foundations. Comparative review highlights the need for updated design procedures to prevent cracks. Keywords: Foundation Design, Settlement Analysis, Structural Strength, Differential Settlement, Crack Prevention